Little known Tyto owls of Wallacea - Bishop, K David (KUKILA, 1989)
During the preparation of The Guide to the Birds of Wallacea, and a review of the conservation and status of Wallacea's endemic birds, it became clear that reviews of little know species or species groups would perhaps aid those species' conservation by drawing attention to them. Secondly such accounts would also provide a useful resource to the growing number of field workers in this, until recently, sadly neglected region. This first account deals with three virtually unknown Tyto Owls endemic to Wallacea.